Performance evaluation of alkali-activated coal-ash aggregate in concrete. Issue 1 (15th March 2018) - Menon, Sreekesh U.; Anand, Kalpathy Balakrishnan; Sharma, Anil Kumar
Abstract : This paper discusses the utilisation of coal-ash (CA) mixtures (bottom ash (BA) and fly ash (FA)) as aggregates for concrete. An optimised mix of BA to FA of 60:40 could produce a basic dense mix of CA suited for aggregates. The aggregates were prepared by pelletisation followed by cold bonding, using the optimised mix blended with cement as a binder. The influence of chemical activators – namely, sodium sulfate and calcium hydroxide – for enhancing, respectively, the reactivity of the CA mix and the pelletisation efficiency was explored in the study. For comparison, two types of aggregates were produced with a higher proportion of either BA or FA. Aggregates were tested for physical and mechanical properties; microstructural and mineralogical aspects were explained through scanning electron microscopy and X-ray diffraction analysis. The performance of CA aggregate concrete and normal concrete were investigated using compressive strength testing. The curing sensitivity of CA aggregate concrete was assessed under different curing regimes – namely, water, air and sealed.